2003
DOI: 10.1007/s00210-003-0771-y
|View full text |Cite
|
Sign up to set email alerts
|

Gliadin increases iNOS gene expression in interferon-γ-stimulated RAW 264.7 cells through a mechanism involving NF-κB

Abstract: Nitric oxide (NO) plays an important role in the pathogenesis of the histological changes seen in coeliac disease. We have investigated the effect of peptic-tryptic digest of gliadin (Pt-G) and gliadin (G) on inducible nitric oxide synthase (iNOS) protein expression in RAW 264.7 macrophages stimulated with interferon-gamma (IFN-gamma). Pt-G and G enhanced in a concentration and time-dependent manner NO production by IFN-gamma-stimulated RAW 264.7 cells. The increase of iNOS protein expression was correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…Additionally, gliadin increased the binding activity of NF-B/DNA, the degradation of IB␣ and the nuclear translocation of p50 and p65 subunits. 25 With these findings we have confirmed that by using a non-toxic (20 mM) supplementation of ascorbate to biopsy culture challenged with gliadin, the gliadin-induced production of nitrites is inhibited. The effects of gliadin are probably mediated by iNOS, and ascorbate acts blocking its pathway.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Additionally, gliadin increased the binding activity of NF-B/DNA, the degradation of IB␣ and the nuclear translocation of p50 and p65 subunits. 25 With these findings we have confirmed that by using a non-toxic (20 mM) supplementation of ascorbate to biopsy culture challenged with gliadin, the gliadin-induced production of nitrites is inhibited. The effects of gliadin are probably mediated by iNOS, and ascorbate acts blocking its pathway.…”
Section: Discussionsupporting
confidence: 71%
“…The effects of gliadin are probably mediated by iNOS, and ascorbate acts blocking its pathway. 25,31 The expression levels of the cytokines IFN␥, TNF␣, IFN␣, and IL-6 are decreased to below those levels observed in basal cultures (Fig. 2).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous studies have suggested the possibility that gliadin, the immunologically active component of wheat gluten associated with CD (2), has the capacity to activate cytokine production in monocytes and macrophages (43)(44)(45). To confirm and extend these findings, the expression of a panel of proinflammatory genes known to be up-regulated by LPS was measured in murine peritoneal macrophages treated with concentrations of PT-gliadin or peptides derived from gliadin (p31-43 or 33-mer) that have been reported previously to be either immunomodulatory or cytotoxic (43)(44)(45).…”
Section: Gliadin Activation Of Proinflammatory Cytokine Gene Expressimentioning
confidence: 99%
“…The results of various investigations suggest that gliadin disturbs the pro-oxidant-antioxidant balance in small intestinal mucosa of affected persons through overproduction of ROS (Boda et al, 1999;Dugas et al, 2003). Several in vitro studies have also reported redox imbalance and increased levels of free radicals after exposure of cells to gliadin (Dolfini et al, 2002;Maiuri et al, 2003;Rivabene, 1999;Tucková et al, 2002).…”
Section: Oxidative Stress and Antioxidant Status Of Patients With Celmentioning
confidence: 99%